Dimethyloxalylglycine Attenuates Steroid-Associated Endothelial Progenitor Cell Impairment and Osteonecrosis of the Femoral Head by Regulating the HIF-1α Signaling Pathway - Wenkai Shao; Zilin Li; Bo Wang; Song Gong; Ping Wang; Beite Song; Zhixiang Chen; Yong Feng (Biomedicines, 2023)
Endothelial impairment and dysfunction are closely related to the pathogenesis of steroid-associated osteonecrosis of the femoral head (SONFH). Recent studies have showed that hypoxia inducible factor-1α (HIF-1α) plays a crucial role in endothelial homeostasis maintenance. Dimethyloxalylglycine (DMOG) could suppress HIF-1 degradation and result in nucleus stabilization by repressing prolyl hydroxylase domain (PHD) enzymatic activity. Our results showed that methylprednisolone (MPS) remarkably undermined biological function of endothelial progenitor cells (EPC) by inhibiting colony formation, migration, angiogenesis, and stimulating senescence of EPCs, while DMOG treatment alleviated these effects by promoting HIF-1α signaling pathway, as evidenced by senescence-associated β-galactosidase (SA-β-Gal) staining, colony-forming unit, matrigel tube formation, and transwell assays. The levels of proteins related to angiogenesis were determined by ELISA and Western blotting. In addition, active HIF-1α bolstered the targeting and homing of endogenous EPCs to the injured endothelium in the femoral head. Histopathologically, our in vivo study showed that DMOG not only alleviated glucocorticoid-induced osteonecrosis but also promoted angiogenesis and osteogenesis in the femoral head as detected by microcomputed tomography (Micro-CT) analysis and histological staining of OCN, TRAP, and Factor Ⅷ. However, all of these effects were impaired by an HIF-1α inhibitor. These findings demonstrate that targeting HIF-1α in EPCs may constitute a novel therapeutic approach for the treatment of SONFH.